ANALISIS SEMIOTIKA PADA COVER MAJALAH TEMPO EDISI TANGGAL 23 FEBRUARI-1 MARET 2015 - Marselin Diana; Retno Dyah Kusumastuti (SEMIOTIKA: Jurnal Komunikasi, 2016)
This study was conducted to determine the meaning of what is entailed and what message to be conveyed to the magazine cover photo Tempo 23 February-1 March 2015. Data collection techniques are from raw data/archive, observation and documentation. By using political communication and theories of Charles Sander Pierce as the basic theory, this study reveales signs of icons, index, and symbol. Icon is a sign that is similar to the object it represents. Also, a sign has characteristics similar to what was intended. The index is a sign that has a causal relationship with what it represents. Symbol is a sign that convention, regulations or agreements agreed refers to the theory of meaning as a concept. Key Informants in this study is Eko Punto as Design Editor of Tempo magazine. From the cover of ‘Tempo’ magazine (23 February-1 March 2015 edition), featuring characters who are in the vortex of cases Budi Gunawan.Key words: Icon, Index, symbol